Optimizing Extractability, Phytochemistry, Acute Toxicity, and Hemostatic Action of Corn Silk Liquid Extract - Zead Helmi Abudayeh; Uliana Karpiuk; Viktoriia Kyslychenko; Qais Abualassal; Loay Khaled Hassouneh; Sami Qadus; Ahmad Talhouni (Journal of Chemistry)
The technological parameters and quality indicators of corn silk were evaluated in this study: specific density, volumetric density, bulk density, porosity, spatial layer, free volume of the layer, the absorption coefficient, weight loss on drying, and extractives. The technology for obtaining a liquid extract of corn silk was developed. The most effective extractant was discovered to be 40% ethanol, with an extraction time of 120 minutes. The qualitative composition and quantitative content of the major groups of biologically active substances (BAS) in the obtained liquid extract were determined. The qualitative composition of the main groups of BAS was determined by conventional chemical reactions. This extract contained free reduced sugars, glycosides (bound reduced sugars), phenols, tannins, flavonoids, saponins, and hydroxycinnamic acids. The quantitative content of phenolic compounds was performed by UV-vis-spectrophotometry. Total phenols, tannins, flavonoids, and hydroxycinnamic acids had quantitative contents of 8.25 ± 0.33%, 1.4 ± 0.03%, 2.20 ± 0.06%, 3.30 ± 0.13%, respectively. The acute toxicity study was carried out with a single intragastric administration to outbred unanesthetized white rats of both sexes. Duration of observation of animals was 14 days. It was revealed that corn silk extract at doses of up to 5.0 ml/kg is safe. A single injection of a liquid extract has no effect on internal organs when compared to a control group. Corn silk liquid extract’s hemostatic efficacy was assessed using blood clotting time, prothrombin time, and blood clot retraction index. The corn silk liquid extract reduces blood coagulation time, decreases prothrombin time, and increases the blood clot retraction index. According to these findings, corn silk liquid extract is rich in phytochemicals and possesses a potential therapeutic effect on bleeding disorders. Furthermore, it could be used in the pharmaceutical sciences industry to develop medicines for testing in the treatment of various diseases.